Short Cantilever Rock Beam Structure and Mechanism of Gob-Side Entry Retaining Roof in Reuse Period - Jingke Wu; Yun Dong; Jiarui Chen; Chunlei Zhang; Wei Yin; JiHua Zhang; Yongzhen Cheng (Shock and Vibration)
In the reuse stage of a gob-side entry retaining, failure of the structure and stability of the main roof have a significant effect on the safety of the advanced support and ventilation space at the working face. In this study, field investigation, theoretical analysis, and industrial experimentation were performed to analyse the fracture characteristics and formation process of the gob-side entry retaining roof during the reuse period. A dynamic-equilibrium mechanical model of the main roof structure is presented and the formation mechanisms of different types of short cantilever rock beam structures are clarified. The following major conclusions are drawn: (1) Three types of short cantilever rock beam structures occur in the main roof of a gob-side entry retaining during the reuse period, namely, the “short cantilever-articulated rock beam” structure, “short cantilever step rock beam (type I)” structure, and “short cantilever step rock beam (type II)” structure. (2) The stability criterion for these three short cantilever rock beam structures was also determined; that is, when the sliding instability coefficient K ≥ 1, the short cantilever-articulated rock beam structure will form, and when the sliding instability coefficient K < 1, the short cantilever step rock beam (type I or II) will form. (3) The governing law for the thicknesses of the main roof, immediate roof, and coal seam of the short cantilever rock beam structure was clarified; namely, the K-value gradually increases with increases in the thickness of the coal seam, drops sharply and then decreases gradually with increases in the thickness of the main roof, and decreases slowly with increases in the thickness of the immediate roof. The research results were validated at the gob-side entry retaining project in the Huainan mining area and have theoretical significance and reference value for roadway support projects with similar conditions.